1994
DOI: 10.1172/jci117023
|View full text |Cite
|
Sign up to set email alerts
|

alpha-Fucose-mediated binding and degradation of tissue-type plasminogen activator by HepG2 cells.

Abstract: The glycoprotein tissue-type plasminogen activator (t-PA) is subject to hepatic clearance in humans. Here, the interaction of t-PA with a well-differentiated hepatoma cell line (HepG2) was examined. Suspended HepG2 cells bound '25I-t-PA in a specific, saturable, and reversible fashion through a Ca2'-dependent, active site-independent mechanism. Binding isotherms indicated a high affinity system with a single class of saturable binding sites (Kd 39 nM; maximum binding capacity 493,000 sites per cell). Bound t-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 58 publications
1
31
0
Order By: Relevance
“…In competition experiments including monosaccharides up to 20 mM or 10 mg/ml ovalbumin in kinetic assays, normal patterns of stimulation were observed with no detectable inhibition over a range of cell densities from 0 to 3 ϫ 10 7 cells/ml. These levels of monosaccharides have previously been shown to inhibit binding of tPA to glycosylation sitespecific cell surface receptors (27). Our results indicate that lack of glycosylation has an indirect effect on stimulation of tPA activity by cells.…”
Section: Resultssupporting
confidence: 61%
“…In competition experiments including monosaccharides up to 20 mM or 10 mg/ml ovalbumin in kinetic assays, normal patterns of stimulation were observed with no detectable inhibition over a range of cell densities from 0 to 3 ϫ 10 7 cells/ml. These levels of monosaccharides have previously been shown to inhibit binding of tPA to glycosylation sitespecific cell surface receptors (27). Our results indicate that lack of glycosylation has an indirect effect on stimulation of tPA activity by cells.…”
Section: Resultssupporting
confidence: 61%
“…Lp(a) is also found in rhesus monkeys, although the apo(a) moiety of this Lp(a) differs in several respects from human apo(a), including an inactive lysine-binding domain at K4 37 and a modification of the RGD peptide sequence at K4 35 of human apo(a). 21 - 32 The data in Fig 3 show that foam cells degraded rhesus monkey Lp(a) to the same degree as human (fast isoform) Lp(a).…”
Section: Degradation Of Different Forms Of Lp(a) By Foam Cellsmentioning
confidence: 92%
“…21 - 32 The data in Fig 3 show that foam cells degraded rhesus monkey Lp(a) to the same degree as human (fast isoform) Lp(a). Thus, neither an active K4 37 lysine-binding domain nor an intact K4 35 RGD sequence appears to be necessary for interaction with the foam cell Lp(a) receptor activity.…”
Section: Degradation Of Different Forms Of Lp(a) By Foam Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that annexin II (AII) is also capable of binding carbohydrates however this work is still in preliminary stages. Previously, the binding of tissue-type plasminogen activator (t-PA) was shown to bind HepG2 cells, however, following enzymatic removal of -fucose residues on t-PA, this binding was dramatically decreased [100]. Subsequently, AII has been shown to be a cell surface receptor for t-PA [101].…”
Section: Galectins Annexins and Epithelial Injury -Repairmentioning
confidence: 99%